Pengaruh Nitrogen Cair terhadap Morfologi dan Jumlah Fibroblas pada Tendon Patela Tikus Wistar Jantan - Isma, Satria Pandu Persada; Norahmawati, Eviana; Irsan, Istan Irmansyah; Asmiragani, Syaifullah; Phatama, Krisna Yuarno; Adiwignyo, Dandy Drestanto; Pratama, Yudit Alfa` (Jurnal Biomedika dan Kesehatan, 2025)
Background Cryoablation with liquid nitrogen has shown promise in treating bone sarcomas, but its effects on fibroblast morphology and viability in ligament tissue remain unclear. This study aims to evaluate the effects of liquid nitrogen on fibroblasts in the patellar tendon ligament of male Wistar rats. Methods This experimental study used 24 male Wistar rats (6 months old, 300-400 grams), randomly divided into four groups. The control group was not exposed to liquid nitrogen, while the experimental groups were exposed for 1, 5, and 10 minutes, respectively. After 7 days of acclimatization, the rats were exposed to liquid nitrogen and then euthanized. The patellar tendon ligaments were collected for histological analysis, stained with Hematoxylin-Eosin, and examined under a microscope. Statistical analysis was performed using One-Way ANOVA, followed by Tukey post hoc tests to determine significant differences among exposure times. Results Significant changes in fibroblast morphology and count were observed with increasing exposure time. One-way ANOVA revealed significant differences (p < 0.001) in fibroblast count and morphological alterations across exposure groups. Tukey post hoc tests showed that a 10-minute exposure resulted in substantial reductions in fibroblast count and viability, accompanied by progressive morphological changes as exposure time increased. Discussion Exposure to liquid nitrogen significantly affects fibroblast cells, and longer exposure times lead to more severe cellular damage. Exposure duration should be carefully controlled during cryotherapy to optimize therapeutic benefits. Conclusions Exposure to liquid nitrogen adversely affects fibroblast cells in the patellar tendon ligament, with prolonged exposure resulting in decreased cell viability and morphological changes.